Gender Equality in Islamic Boarding Schools: Paulo Freire's Philosophical Review of the Education System Fathul Muin Banyumas Islamic Boarding School - Harisman, Harisman; Maftuchah, Farichatul (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2024)
Islamic boarding schools are seen as a non-formal educational institution that holds religious-based programs for its students. Nevertheless, Islamic boarding schools are often used as a legitimacy of gender injustice. This issue definitely needs to be reviewed by looking directly at the actual reality of education in it and its influence on the thinking of the students regarding gender equality. Thus, this study took the subject of Fathul Muin Islamic boarding school research by using Paulo Freire's philosophy of humanism because with his philosophical theory it can be studied about the role of Islamic Boarding School in providing awareness, especially for female students about gender equality and justice of rights. The results show that Fathul Muin Islamic boarding school education greatly influences the mindset of its students. The results of the interviews show that there has been an awareness of gender equality. However, the thing that needs to be criticized lies in the learning patterns of Islamic boarding schools which are not much different from other Islamic boarding schools, so reforms need to be carried out as a process towards values of liberation, humanism and equality.